Molecular docking analysis of flavonoid compounds from gandaria (Bouea macrophlla Griff) as potential alpha-glucosidase inhibitors - Azzahrah, Qurrota A’yun; Novelina, Laras; Rosviena, Nyi Ayu Fayza; Saabirah, Ghania Parsa; Adilla, Annisa Rahma; Saeli, Pinka Mustika; Uswatunhasanah, Putri; Auli, Winni Nur; Saputro, Anjar Hermadi (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2024)
Diabetes mellitus represents a significant metabolic disorder with elevated global prevalence, necessitating development of effective antidiabetic therapies. This study investigates flavonoid compounds from gandaria (Bouea macrophylla Griff) as potential α-glucosidase inhibitors through molecular docking analysis. Eight flavonoid compounds were evaluated against human α-glucosidase enzyme (PDB ID: 2QMJ) using AutoDock Tools version 1.5.6. The methodology achieved validation with an RMSD value of 1.98 Å, confirming computational reliability. Lipinski's Rule of Five assessment identified four compounds meeting drug-likeness criteria for analysis. Quercetin demonstrated the strongest binding affinity among tested compounds with a binding energy of -4.72 kcal/mol, compared to the native ligand N-acetylglucosamine at -5.12 kcal/mol. Interaction analysis revealed quercetin formed significant hydrogen bonds with key active site residues including Lys389, Asn393, and Asn417, indicating potential competitive inhibition mechanisms. All flavonoid compounds exhibited consistent binding patterns with Lys389 serving as a critical interaction site. These computational findings establish quercetin as the most promising flavonoid candidate for α-glucosidase inhibition, supporting its potential as a natural antidiabetic agent.